Dissecting MicroRNA–mRNA Regulatory Networks Underlying Sulfur Assimilation and Cadmium Accumulation in Poplar Leaves. (17th July 2020) - Shi, Wenguang; Liu, Wenzhe; Ma, Chaofeng; Zhang, Yuhong; Ding, Shen; Yu, Wenjian; Deng, Shurong; Zhou, Jing; Li, Hong; Luo, Zhi-Bin
Abstract: The process of cadmium (Cd) accumulation and detoxification under different sulfur levels remains largely unknown in woody plants. To investigate the physiological and transcriptomic regulation mechanisms of poplars in response to different sulfate (S) supply levels and Cd exposure, we exposed Populus deltoides saplings to one of the low, moderate and high S levels together with either 0 or 50 µM Cd. Cd accumulation was decreased in low S-treated poplar leaves, and it tended to be increased in high S-supplied leaves under the Cd exposure condition. Sulfur nutrition was deficient in low S-supplied poplars, and it was improved in high S-treated leaves. Cd exposure resulted in lower sulfur level in the leaves supplied with moderate S, it exacerbated a Cd-induced sulfur decrease in low S-treated leaves and it caused a higher sulfur concentration in high S-supplied leaves. In line with the physiological changes, a number of mRNAs and microRNAs (miRNAs) involved in Cd accumulation and sulfur assimilation were identified and the miRNA–mRNA networks were dissected. In the networks, miR395 and miR399 members were identified as hub miRNAs and their targets were ATP sulfurylase 3 ( ATPS3 ) and phosphate 2 ( PHO2 ), respectively. These results suggest that Cd accumulation and sulfur assimilation are constrained by low and enhanced by high S supply, and Cd toxicity is aggravated by low and relieved by high S in poplar leaves, and that miRNA–mRNA regulatory networks play pivotal roles in sulfur-mediated Cd accumulation and detoxification in Cd-exposed poplars.